2007
DOI: 10.1101/lm.430907
|View full text |Cite
|
Sign up to set email alerts
|

Memory for context becomes less specific with time

Abstract: Context memories initially require the hippocampus, but over time become independent of this structure. This shift reflects a consolidation process whereby memories are gradually stored in distributed regions of the cortex. The function of this process is thought to be the extraction of statistical regularities and general knowledge from specific experiences. The current study examined this idea in mice by measuring the specificity of context memories during consolidation. In the first experiment, separate gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
278
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(314 citation statements)
references
References 38 publications
32
278
4
Order By: Relevance
“…These findings are in line with what is seen in GABA B(1a) KO mice; they display precise memory recall for contextual fear or object recognition 2 h, but not 24 h after training (Cullen et al, 2014). Several studies demonstrate the importance of the hippocampus in context memory precision (Ruediger et al, 2011;Wiltgen and Silva, 2007;Wiltgen et al, 2010;Winocur et al, 2007). According to the transformation hypothesis of memory function over time, detailed context-specific memories are initially dependent on the hippocampus, but are transformed into schematic (less specific) memories as they are stored in the neocortex, resulting in generalized memory recall (Frankland et al, 2006;Frankland et al, 2001;Kim and Fanselow, 1992;McGaugh, 1966;Vetere et al, 2011;ZolaMorgan and Squire, 1990).…”
Section: Gabab(1a) Receptors and Fear Generalizationsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are in line with what is seen in GABA B(1a) KO mice; they display precise memory recall for contextual fear or object recognition 2 h, but not 24 h after training (Cullen et al, 2014). Several studies demonstrate the importance of the hippocampus in context memory precision (Ruediger et al, 2011;Wiltgen and Silva, 2007;Wiltgen et al, 2010;Winocur et al, 2007). According to the transformation hypothesis of memory function over time, detailed context-specific memories are initially dependent on the hippocampus, but are transformed into schematic (less specific) memories as they are stored in the neocortex, resulting in generalized memory recall (Frankland et al, 2006;Frankland et al, 2001;Kim and Fanselow, 1992;McGaugh, 1966;Vetere et al, 2011;ZolaMorgan and Squire, 1990).…”
Section: Gabab(1a) Receptors and Fear Generalizationsupporting
confidence: 87%
“…To date, theories of memory precision all share the idea that the passage of time is required in order for generalized responding to occur (Biedenkapp and Rudy, 2007;Jasnow et al, 2012;Lynch et al, 2013;Matynia et al, 2008;Wiltgen and Silva, 2007;Winocur et al, 2007). The current data suggest, in some cases, the loss of memory precision does not require a significant passage of time (ie, several or more days) and can be dependent upon the maintenance of the originally formed memory trace during memory consolidation.…”
Section: Gabab(1a) Receptors and Fear Generalizationmentioning
confidence: 58%
“…Interestingly, fear was absent early after training, but it was evident in remote memories, when animals were exposed to a novel context. As previously proposed (Wiltgen and Silva, 2007), this suggests that contextual fear memories generalize to other environments with the passage of time. In addition, MDZ administration after exposure to the nonassociated environment does not affect fear memory regardless of the interval between training and exposure to B.…”
Section: Discussionsupporting
confidence: 75%
“…A number of studies have described how contextual fear memory becomes less context-specific over time, showing that animals increasingly generalize conditioned responding to novel contexts (Biedenkapp and Rudy, 2007;Ruediger et al, 2011;Wiltgen and Silva, 2007;Wiltgen et al, 2010;Winocur et al, 2009;Winocur et al, 2007). Similarly, we found that rats did not generalize conditioned fear responding to a novel context when tested 3 days after training, but expressed generalized fear in the novel context when tested 30 days after training.…”
Section: Discussionsupporting
confidence: 67%
“…This posited role of the hippocampus in supporting context memory precision is supported by recent studies showing (a) that inactivation of the dorsal hippocampus disrupts the expression of context-specific fear memory, but not the expression of generalized fear memory (de Oliveira Alvares et al, 2012;Wiltgen et al, 2010) and (b) that inhibitory connectivity in the mossy fibers of the dorsal hippocampus are critical for maintaining context-specificity of contextual fear memory (Ruediger et al, 2011). Previous studies have demonstrated that brief re-exposure to a training context at remote time points can reinstate context-specific memory expression, an effect that lasts from 1 h (Zhou and Riccio, 1994), up to at least 24 h (Wiltgen and Silva, 2007). This brief reversal of fear generalization may be mediated by a transient recruitment of the hippocampus, possibly as part of a memory updating process.…”
Section: Discussionmentioning
confidence: 99%